2010
DOI: 10.1631/jzus.b1000055
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of high-affinity rabbit monoclonal antibodies for ciprofloxacin and development of an indirect competitive ELISA for residues in milk

Abstract: Abstract:A convenient competitive enzyme-linked immunosorbent assay (ELISA) for ciprofloxacin (CPFX) was developed by using rabbit monoclonal antibodies (RabMAbs) against a hapten-protein conjugate of CPFX-bovine serum albumin (BSA). The indirect competitive ELISA of CPFX had a concentration at 50% inhibition (IC 50 ) of 1.47 ng/ml and a limit of detection (LOD) of 0.095 ng/ml. The mAb exhibited some cross-reactivity, however, not so high with enrofloxacin (28.8%), ofloxacin (13.1%), norfloxacin (11.0%), flero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…After an elaborate antibody validation benzoylecgonine, MDMA and methadone were detectable and quantifiable specifically and sensitively. Comparing the results to other competitive immunoassays for substances like antibiotics (Huang et al, 2010;Jiang et al, 2013;Wang et al, 2015), similar detection limits and CVs were obtained. In relation to one of the standard application of immunoassays for drug abuse (lateral flow assays) better detection limits and quantification could be reached (Attema-de Jonge et al, 2012;Taylor and Pizzo, 2004).…”
Section: Discussionsupporting
confidence: 68%
“…After an elaborate antibody validation benzoylecgonine, MDMA and methadone were detectable and quantifiable specifically and sensitively. Comparing the results to other competitive immunoassays for substances like antibiotics (Huang et al, 2010;Jiang et al, 2013;Wang et al, 2015), similar detection limits and CVs were obtained. In relation to one of the standard application of immunoassays for drug abuse (lateral flow assays) better detection limits and quantification could be reached (Attema-de Jonge et al, 2012;Taylor and Pizzo, 2004).…”
Section: Discussionsupporting
confidence: 68%
“…The immunogen ENFX-BSA and the coating antigen ENFX-OVA were both prepared by the carbodiimide active ester method (Huang et al, 2010). A total of 9.12 mg (0.03 mmol) ENFX, 9.53 mg (0.06 mmol) of EDC and 3.21 mg (0.03 mmol) of NHS were added to 1.0 mL of dry dimethylformamide in order.…”
Section: Immunogen and Antigen Synthesismentioning
confidence: 99%
“…Furthermore, studies have shown that food-processing methods such as cooking and pasteurisation do not affect the level of FQs in food since residues remain relatively stable during heating (Al-Mustafa and Al-Ghamdi, 2000;Lolo et al, 2006;Roca, Castillo, Marti, Althaus, & Molina, 2010). As a result of these concerns, many countries and organisations including the European Union (EU), USA, Japan, People's Republic of China (PRC), and Food and Agriculture Organization of the United Nations (FAO) have set maximum residue limits (MRLs) for several quinolones and FQs (Huang et al, 2010). For example, among the EU members, an MRL of 100 µg kg −1 has been recommended for bovine muscle, fat and milk, 200 µg kg −1 and 300 µg kg −1 for bovine kidney and liver, respectively (European Commission, 2010) for ENFX.…”
Section: Introductionmentioning
confidence: 99%
“…The solution was stored at -20°C. An ENR-OVA conjugate was prepared as a modified previous paper (Huang et al, 2010) and the mixed-anhydride technique route was as shown in Figure 2.…”
Section: Synthesis Of Immunogen and Coating Antigenmentioning
confidence: 99%